If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -73898x + 3E + 6 Reorder the terms: y = 6 + 3E + -73898x Solving y = 6 + 3E + -73898x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 6 + 3E + -73898x
| 9.8x+85.71=-10.2x+85.19 | | x*2-144=0 | | 6n+13=3x+14 | | (2y/3)-(13/2)=1/6 | | 3y=2y+34 | | sin^2(x)-3sin(x)+1=0 | | -4x+15=x^2 | | 36x-96-15x-15+140-20x=80-20x-48x-30 | | 8+2w+w^2= | | 3n^2-16n+12=0 | | sin^2(2x)-3sin(2x)+1=0 | | 3(16-18)/2(10) | | (2v+1)(4+v)=0 | | .4(x+2)=1.4(x+1.5) | | 72x-120-1-32x-16+12x+36=30x-1 | | -4(t-7)-(t+4)=7 | | (4x+12)=0 | | x^2+rx-s=0 | | 4(x-3)-7=3(x+2)+6x | | -8y+6x+9=0 | | 2(1+x)=(25825000) | | 230=-5(6p-4) | | 7i+6=-6 | | 11x-3y=54 | | 9+7(x-6)=3-2(x-9) | | P=4c-(20+c) | | 2x+2=2x+4 | | y=4x^2-20x+25 | | (1.1+4.7)x=22.5 | | x=.666x+2 | | 8b^4-b^3-b^4+4b^3-4= | | x+53=x |